Influence of guaranteed power supply service on competitive power market and compensation mechanism design. Issue 1 (January 2021) - Wang, Dongfa; Ding, Weibing; Gao, Feng; Xu, Yang; Hu, Jiahua
Abstract: In the modern power market system, it is necessary to establish a mature power supply guarantee service mechanism to protect the rights and interests of all users, realize the reasonable allocation of power resources and achieve the "Pareto improvement" of social welfare. Based on a broader definition of guaranteed power supply service, this paper clarifies the scope and mode of guaranteed power supply service, calculates the power supply cost and market clearing electricity of guaranteed power supply service, and designs a corresponding compensation mechanism system to promote the sustainable development of guaranteed power supply service. In the long run, guaranteed power supply service should return to the market mechanism, pricing based on "power supply cost + reasonable profit", and become an essential part of the competitive power market.